From Lady’s-slipper Orchid to Christ’s Crown. Morpho-Semantic Analysis of Religiously Motivated Phytonyms in French, Italian and Serbian Language - Milica Mirić (University of Belgrade, 2019)
Folk plant names as an extremely various layer of each language lexis, are the subject of study in many disciplines, including linguistics. In this paper, denominational procedures in naming plants in French, Italian and Serbian language are examined on the morphological, semantic and motivational plan, using onomasiological analysis. Due to the great importance that man has always attached to religion, the folk nominator has found in its numerous inducements for giving names to plants. For this reason, the religiously motivated phytonyms were examined, containing hagionyms Mother of God, God and Christ, or who are in the indirect semantic connection with them. Research results show that the term "Mother of God" is the most frequent source of motivation in all three languages, and that the investigated phytonyms relate mostly to medicinal plants. The metaphorical denomination was conducted on morphological or utilization characteristics of plants, and many legends in which individual plant species are linked to the examined Christian concepts. By comparing phytonyms in these three languages, it has been determined that these are often created morphologically and semantically similarly or in the same way in the French and Italian language, while Serbian is different in that respect. The causes of this state lie in the different structure of Romance (analytical) versus Slavic (synthetic) languages, but also in the specifics of West European and South Slavic culture and civilization.